Noise Exposure on Pediatric Inpatient Units. (September 2016) - Daraiseh, Nancy M.; Hoying, Cheryl L.; Vidonish, William P.; Lin, Li; Wagner, Michael
Abstract : BACKGROUND: Noise is a problem placing registered nurses (RNs) at risk for safety events, decreased job performance, fatigue, irritability, and hearing loss. OBJECTIVE: The purpose of this study is to measure noise levels and sources on pediatric inpatient units as well as to explore the health impact of noise on RNs. METHODS: This was a descriptive nonexperimental study with 65 pediatric RNs from 14 units. Noise (levels, source, location, and activity), heart rate (HR), and stress were measured. Correlations between sound pressure levels (SPLs), HR, and stress were examined. RESULTS: Mean (SD) SPLs were 75.8 (8.9) dBA and were significantly higher than SPLs for patients. Noise was significantly associated with HR but not with time in tachycardia or stress. Primary sources of noise were employee conversations in patient rooms. CONCLUSIONS: On all units, SPLs exceeded protection agency guidelines. Cost-prohibitive structural changes underscore the importance of using behavioral and culture modification to reduce noise.